2022
DOI: 10.1038/s41467-022-29164-0
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell transcriptomic analysis suggests two molecularly distinct subtypes of intrahepatic cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (iCCA) is a highly heterogeneous cancer with limited understanding of its classification and tumor microenvironment. Here, by performing single-cell RNA sequencing on 144,878 cells from 14 pairs of iCCA tumors and non-tumor liver tissues, we find that S100P and SPP1 are two markers for iCCA perihilar large duct type (iCCAphl) and peripheral small duct type (iCCApps). S100P + SPP1− iCCAphl has significantly reduced levels of infiltrating CD4+ T cells, CD56+ NK cells, and increase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 63 publications
7
77
0
Order By: Relevance
“…Indeed, this question may have been resolved if Wang et al, [ 13 ] during the effort to determine how consistent their murine single‐cell types resemble those found in human iCCA, had incorporated their data together with the recently suggested iCCA subtype markers S100 calcium binding protein P and SPP1. [ 17 ] In this study, the authors concluded that the peripheral‐type iCCA comprises tumor cells at different differentiation states, including albumin‐positive hepatocytic and inhibitor of DNA‐binding 3–positive cells, which suggests a hepatoblast status. It should be mentioned that after obtaining a total of 51,897 single cells representing epithelial, immune, and stromal macrophages from days 10, 17, and 31, the Sankey diagram linking mouse and human cell types suggests that cells obtained at day 10 and 17 mostly correspond to cells observed in the human tumor‐adjacent tissues.…”
Section: Figurementioning
confidence: 87%
“…Indeed, this question may have been resolved if Wang et al, [ 13 ] during the effort to determine how consistent their murine single‐cell types resemble those found in human iCCA, had incorporated their data together with the recently suggested iCCA subtype markers S100 calcium binding protein P and SPP1. [ 17 ] In this study, the authors concluded that the peripheral‐type iCCA comprises tumor cells at different differentiation states, including albumin‐positive hepatocytic and inhibitor of DNA‐binding 3–positive cells, which suggests a hepatoblast status. It should be mentioned that after obtaining a total of 51,897 single cells representing epithelial, immune, and stromal macrophages from days 10, 17, and 31, the Sankey diagram linking mouse and human cell types suggests that cells obtained at day 10 and 17 mostly correspond to cells observed in the human tumor‐adjacent tissues.…”
Section: Figurementioning
confidence: 87%
“…Through scRNA-seq analysis of intrahepatic cholangiocarcinoma, S100P and SPP1 are regarded as two biomarkers for two intrahepatic cholangiocarcinoma molecular subtypes. CREB3L1, which is upregulated in S100P + SPP1− intrahepatic cholangiocarcinoma tumor cells, can facilitate the invasion of S100P + SPP1− perihilar large duct type tumor cells by directly targeting S100P ( Song et al, 2022 ). However, the investigation of CREB3L1 in human malignancies is still of absence to date, and the results of present studies are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, in CRC, the angiogenesis subtype assumes a prominent place, and thus, SPP1 + macrophages exhibit a protumor phenotype. In addition, previous studies found that SPP1 was associated with a better immunotherapy response in lung cancer [57] and a favorable prognosis in cholangiocarcinoma [58]. In non-small-cell lung cancer, researchers defined an activation module consisting of PDCD1 + CXCL13-activated T cells, IgG plasma cells, and SPP1 + macrophages, and a high baseline of this module was related to a better immune response [57].…”
Section: Discussionmentioning
confidence: 99%